Attitudes towards telework for continuity planning in Japan - Bourna Maria; Mitomo Hitoshi (International Telecommunications Society (ITS), 2012)
This paper examines the suitability of telework for business continuity planning (BCP) in Japan by looking at how views on telework are shaped by demographic characteristics, organizational culture, and individuals' use of technology. The study surveyed regular employees with experience of the 2011 Tohoku earthquake (n=39) and their responses were analyzed using cross-tabulation analysis. The results showed generally positive attitudes towards telework, overwhelmingly so with respect to BCP-specific telework. From the survey it was further induced that certain characteristics may be associated with a greater likelihood that an individual will want or choose to telework; these are gender, the presence of dependents, placing reduced value in the role of the workplace, exhibiting consumerization tendencies, and using social media to interact with coworkers, albeit in work-designated profiles. The ability to identify such characteristics, and consequently, find individuals with positive views towards ad hoc telework, can be constructive in increasing the adoption rate of telework for BCP projects.
Keywords: 330; ICT; BCP; consumerization; social media; presenteeism; business culture